A comparative thermodynamic analysis on different exergetic efficiency methods for a solar photovoltaic module. (2017) - Á-zalp, Mehmet; Bayat, Mutlucan
In this paper, a comparative study on the different exergetic performance of a solar photovoltaic (PV) module is presented. The exergetic efficiency of the PV module was obtained as functions of environmental, operational and design parameters, and calculated in four cases. In Case I, electrical exergy, thermal exergy and exergy destructions were considered. In Case II, a novel expression on the calculation of solar exergy was proposed. In Case III, chemical and physical exergy components including enthalpy and entropy concepts were discussed. In Case IV, an empirical expression depending on the power conversion efficiency of the system was used. As a result, the exergy efficiency varied in the range 9.25% to 18.32% in Case I, whereas it varied between 9.41% and 18.34% in Case II. In addition, the exergy efficiency varied from 6.58% to 19.99% in Case III, whereas it varied in the range of 9.30% to 18.89% in Case IV during November 2015.